MAPEAMENTO CONCEITUAL DA INTER-RELAÇÃO ENTRE GESTÃO DO CONHECIMENTO, CAPITAL INTELECTUAL E MÉTRICAS DE QUALIDADE NAS UNIVERSIDADES - Neimar Sousa Pinto Pereira (Universidade Federal de Santa Catarina, 2015)
The new context of the requirements allocated to higher education institutions (HEI) resonates in various dimensions within these organizations. Therefore, this work presents a conceptual resulting after a systematic review mapping about literature application at Knowledge Management (KM), the Intellectual Capital (IC) and Templates or Metric Quality (MQ) applied to the universities. It was intended to understand and identify how GC techniques, IC applications, and the use or adoption of MQ can function as tools to support differential of IES. The literature review was based on articles published in scientific journals of qualified with relevant impact factor. The main contribution of this paper is focused on the preparation of draft integrative mapping of concepts, using a concept map built collaboratively among authors, and in preparation of the conceptual work model mapping derivative as thereof. These models indicate, visually, an occurrence of inter-relationship between concepts which would not be easy disclosure a purely textual context.